Ensino superior no contexto da pandemia da COVID-19: um relato analítico. - Pesce, Lucila (2021)
This article reflects on the difficulties presented to higher education and their confrontations, considering the scenario of the pandemic of COVID-19. Regarding to the methodological approach, the article is classified as an analytical report of the educational actions developed at two universities in São Paulo state, Brazil: a public and a communitarian one. The theoretical framework of the analytical report is based on an intertext between the concept of Communicative Action (Habermas) and Dialogism (Bakhtin). Based on this theoretical framework the article reflects on the hegemonic instrumental rationality which supports a good part of the educational actions in Brazilian higher education, even more so in the context of the pandemic. Through the instrumental rationality, the world of life of the social actors directly involved in the educational processes (students, teachers, managers and educational technicians) is colonized by the system, in this case, the educational system. In opposition to this hegemonic rationality, imbricated to capital, this article reports some educational actions developed by these two universities, based on dialogic premise, in attention to the teachers and students’ world of life that participate in the reported educational actions.